Strategy for Developing Mosque Business Units for Economic Empowerment of the People (Study at the Oman Al-Makmur Mosque) - Al-Abrar T. A, T. Hafidh; Murni, Seri; Maulana, Hafiizh (Universitas Syiah Kuala, 2025)
This research aims to develop a strategy for developing mosque business units to empower the people's economy, with a focus on SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis at the Oman Al-Makmur Mosque. This research uses a descriptive analytical approach to identify weaknesses and opportunities in the context of mosque business units. The SWOT analysis method is applied to evaluate the internal and external conditions of mosques in order to optimize the potential of existing business units. The weakness-opportunity (WO) strategy is an approach used to overcome existing weaknesses by taking advantage of available opportunities. This strategy aims to reduce the impact of internal weaknesses by taking advantage of favorable external conditions, so as to achieve better results in business unit development. The research results show that although the Oman Al-Makmur Mosque faces several weaknesses such as limited capital and human resources, there are significant opportunities to develop business units through the use of community networks and technological support. The proposed WO strategy includes improving management skills, and utilizing technology to increase operational efficiency. By implementing this strategy, it is hoped that the mosque business unit can contribute more to the economic empowerment of the congregation, improve the welfare of the surrounding community, and strengthen the role of mosques in local economic development.